Three new species of Pogonognathellus (Collembola: Tomoceridae)from North America - Park, Kyung-Hwa; Bernard, Ernest C.; Moulton, John K. (Zootaxa, 2011)
Three species of Pogonognathellus Paclt are described from eastern North America: P. belmontorum n. sp. from the southern Appalachians, Alabama and Florida, P. brevifulvus n. sp. from Massachusetts and Michigan, and P. magnibrunneus n. sp. from the southern Appalachians and New York. The first two species are members of the pale/grey clade and the third is a member of the longicornis clade. The setal complexes at the apices of the third and fourth antennal segments are described.